EFFICACY OF MANUAL THERAPY VERSUS CONVENTIONAL PHYSIOTHERAPY IN THE TREATMENT OF CHRONIC LOWER BACK PAIN - Eissa Fahaid S Alshammri, Nawaf Falah Alanazi, Ahmed Shared Joban Al-Anazi, Farhan Faleh Alshammari, Fahad Farhan Hamed Alanazi, Khaled Hassan Al-anazi, (Chelonian Research Foundation, 2022)
Lower back pain is a highly prevalent condition associated with substantial disability and impacts on quality of life. While often managed conservatively, many patients have persistent pain despite treatment. Research suggests manual therapy techniques may enhance outcomes for chronic lower back pain when added to conventional physiotherapy rehabilitation. This randomized controlled trial aimed to compare the efficacy of manual therapy versus conventional physiotherapy alone in reducing pain and disability in patients with chronic lower back pain. 120 patients referred to a rehabilitation hospital in Saudi Arabia with chronic lower back pain were randomly allocated to receive either manual therapy or conventional physiotherapy treatments twice weekly for two months. Primary outcomes measured were pain intensity assessed using the Visual Analogue Scale (VAS) and back-specific disability assessed with the Oswestry Disability Index (ODI). Secondary outcomes encompassed analgesia use and lumbar range of motion. Assessments occurred at baseline, monthly, and at discharge. Results demonstrated that patients receiving manual therapy had significantly greater reductions in mean VAS pain scores (-5.2 vs -3.7, p<0.01) and mean ODI disability scores (-31 vs -22, p<0.05) compared to conventional physiotherapy alone. The manual therapy group also had greater decreases in analgesia use and increases in lumbar range of motion. Findings support incorporating manual therapy techniques as an adjunct to conventional physiotherapy rehabilitation to enhance outcomes for patients with chronic lower back pain. Further research on optimal protocols and long-term effects is warranted.